The mechanical properties of alkali and laccase treated pterocarpus angolensis (mukwa)-polylactic acid (PLA) composites - Setswalo, K.; Oladijo, O.P.; Namoshe, M.; Akinlabi, E.T.; Sanjay, M.R. (International journal of biological macromolecules, 2022)
The desire of producing marketable green bio-composites displaying good functional properties has increased. Biodegradable composites are a subject of interest as they respond to ecological concerns. In this study, an eco-friendly alkali-laccase modification was used to improve the interfacial adhesion of mukwa wood fiber and polylactic acid (PLA) matrix. The untreated and treated mukwa-PLA composites were fabricated via extrusion and compression molding technique and investigated. The mukwa wood fibers and mukwa-PLA composites were characterized by chemical composition, crystallite size, Fourier transform infrared spectroscope (FTIR), mechanical properties, and scanning electron microscope (SEM) respectively. The cellulose content was found to increase, while the hemicellulose, lignin, and extractives reduced after the surface modifications. The alkali-laccase, laccase, and alkali modifications increased the tensile strength of the untreated/PLA composites by 12.3 %, 5.2 %, and 3.8 % respectively. The flexural strength of the composites reached a maximum of 95.1 MPa following the alkali-laccase treatment. The alkali-laccase treated composites showed increased impact strength of 53.9 % on the untreated/PLA composites. Good correlations between the crystallite size and the mechanical properties were reported, with the highest R-square (R2) value of 1 found between the impact strength and crystallite size. The modifications strengthened the interaction between mukwa and PLA as more voids, fiber pull-outs, and debonding characteristics were observed on SEM microstructures of untreated/PLA.